(untitled) (Research, Society and Development, 2022)
The Tucuruí Hospital complex comprises three municipal health departments, which have two places for the temporary storage of Health Service Waste (RSS), however these places present inappropriate conditions. The purpose of this article on environmental expertise will be to advise the proper management of RSS, in addition to helping to reduce the risks inherent to the health and safety of workers. It is necessary to point out that the RSS are divided into 5 classes, which are A, B, C, D and E, to facilitate their management. It becomes noticeable that the professionals responsible for managing the RSS at the Tucuruí complex are unaware of the biosafety norms, as well as the health and environmental safety risks. an expert study was carried out, in addition to bibliographic research, to verify the risks associated with temporary disposal. The Environmental Impact Assessment was of great importance for the technical measurement of the environmental impacts inherent to the Tucuruí Complex. Finally, it can be noted that there are great risks of environmental contamination, suggesting immediate adaptation, construction of planned shelters and hiring a qualified company to perform this service.